Change in dermatology practice during crisis and normalization periods after the COVID-19 pandemic and potential problems awaiting us - Çağrı Turan; Ümran Öner; Nurcan Metin (Galenos Publishing House, 2021)
Background and Design: This study aimed to reveal the effects of the crisis period and normalization process after the Coronavirus disease-2019 (COVID-19) pandemic on dermatology practice to anticipate future health problems. Materials and Methods: All patients were enrolled from the dermatology outpatient clinics between February and July 2020 (pre-COVID-19 period, crisis period, and normalization period). Data such as age, sex, application dates, diagnoses, and treatment methods were received from the electronic registration database. Results: The number of patients in the normalization period (32.3%) increased relative to that in the crisis period (11.5%), and it was significantly lower than that before the pandemic (56.2%). Remarkably, the change in the distribution of stress-related diseases, such as idiopathic generalized pruritus, alopecia areata, and herpes zoster, stably paralleled each other and the increase and decrease trends during the crisis and normalization periods, respectively. The increase in the frequency of contact dermatitis, which was not reflected in the crisis period, became evident in the normalization period (p<0.001). No significant change was found in the rate of scabies (p=0.276). However, the number of patients with scabies was remarkably decreased. Conclusion: The decrease in stress-related diseases indicates that social stress started to decrease with normalization. Scabies and venereal diseases, which concern public health, should not be neglected. Disease rates and the number of patients provide an idea about potential problems after the pandemic. Understanding the trends in dermatological diseases and the changing health system during the pandemic will aid in solving future problems.